2009
DOI: 10.1103/physrevb.80.214107
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-driven superplasticity in ceramics: Modeling and comparison with available data

Abstract: The discovery of superplasticity in ceramics polycrystals led to debates about whether or not earlier models developed for metallic polycrystals can apply to these systems. In particular, all existing models require some mobility of lattice or grain-boundary dislocations whereas such activity is not observed in most ceramic systems. A model is presented that accounts for the occurrence of superplasticity in the absence of dislocation motion. It is based on a mechanism of grain-boundary sliding by pure-shear mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…The conventional phenomenological power law creep models that are used to explain (stress) 3 or (stress) 4.5 creep behavior are not relevant for fine‐grained Al 2 O 3 under modest stresses. The most recent attempt to explain these grain size and stress dependencies involves a model that assumes that grain curvature is the driving force for grain sliding, that grain boundaries are dislocation‐free, and that grain‐boundary sliding is accommodated by diffusion. As has been argued earlier, at least for Al 2 O 3 , these assumptions are in doubt, as we believe that such high‐temperature deformation in polycrystalline Al 2 O 3 must involve, at least in part, shear‐driven disconnection migration.…”
Section: High‐temperature Creep Resistance Of Polycrystalline Al2o3mentioning
confidence: 99%
“…The conventional phenomenological power law creep models that are used to explain (stress) 3 or (stress) 4.5 creep behavior are not relevant for fine‐grained Al 2 O 3 under modest stresses. The most recent attempt to explain these grain size and stress dependencies involves a model that assumes that grain curvature is the driving force for grain sliding, that grain boundaries are dislocation‐free, and that grain‐boundary sliding is accommodated by diffusion. As has been argued earlier, at least for Al 2 O 3 , these assumptions are in doubt, as we believe that such high‐temperature deformation in polycrystalline Al 2 O 3 must involve, at least in part, shear‐driven disconnection migration.…”
Section: High‐temperature Creep Resistance Of Polycrystalline Al2o3mentioning
confidence: 99%
“…In recent years, a rapidly growing attention in physics of nanoscale plasticity has been paid to specific microscopic mechanisms/modes of plastic deformation in various nanocrystalline and ultrafine-grained solids; see, e.g. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In nanocrystalline solids, specific deformation modes operate due to the interface and nanoscale effects associated with structural peculiarities of these solids where the grain or crystallite size d is in the nanometer range, and the volume fraction occupied by grain boundaries (GBs) is extremely high; see reviews 16,17 and book. 18 For instance, GBs conduct plastic flow and serve as sources or sinks of lattice dislocations in nanocrystalline metals and ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] In particular, GB sliding and other GB deformation modes effectively come into play in nanocrystalline solids with finest grains having typical sizes d lower than 10-20 nm in wide temperature ranges. [16][17][18] In addition, GB sliding serves as the dominant mode of superplastic deformation at elevated temperatures in nanocrystalline materials, 2,12,18,22,23 ultrafine-grained metals, 24,25 and polycrystals (with the microcrystalline structures characterized by grain sizes being of the order of 10 μm). 12,26 GB sliding is strongly influenced by triple junctions of GBs, and this influence is of critical importance in nanocrystalline and ultrafine-grained solids where the amount of triple junctions is extremely large.…”
Section: Introductionmentioning
confidence: 99%
“…Second, most studies of other zirconia ceramics, particularly those of yttria-zirconia ceramics, have reported that their high-temperature deformation mechanism fits the Ashby-Verrall picture with a stress exponent equal to 2 rather than the expected theoretical value n = 1. This inconsistency has quite recently been resolved with an improved modified version of the Ashby-Verrall model proposed by Gómez-García et al 3 This new model predicts values of 2 or 1 depending on the grain size, stress, testing condition temperature, and the value of the test material's grain boundary energy. In particular, the stress exponent depends on the testing conditions according to the equation…”
Section: Discussionmentioning
confidence: 98%
“…Despite the numerous publications on the topic, it has only been recently that a consistent theory of ceramic superplasticity applicable to zirconia ceramics has emerged. 3 Among the factors governing the superplastic response, a key has repeatedly been reported to be the chemical nature at the boundaries. Indeed, yttrium segregation to the boundaries is known to affect the mechanical behaviour, 4 mostly in a negative sense.…”
Section: Introductionmentioning
confidence: 99%